Continuous Production of Human Epidermal Growth Factor Using Escherichia coli Biofilm - Li, Mengting; Wang, Zhenyu; Zhou, Miao; Zhang, Chong; Zhi, Kaiqi; Liu, Shuli; Sun, Xiujuan; Wang, Zhi; Liu, Jinle; Liu, Dong (Frontiers in Microbiology, 2022)
Increasing demand for recombinant proteins necessitates efficient protein production processes. In this study, a continuous process for human epidermal growth factor (hEGF) secretion by Escherichia coli was developed by taking advantages of biofilm formation. Genes bcsB, fimH, and csgAcsgB that have proved to facilitate biofilm formation and some genes moaE, yceA, ychJ and gshB potentially involved in biofilm formation were examined for their effects on hEGF secretion as well as biofilm formation. Finally, biofilm-based fermentation processes were established which demonstrated the feasibility of continuous production of hEGF with improved efficiency. The best result was obtained from ychJ-disruption that produced an average of 28% higher hEGF secretion. Overexpression of bcsB also showed great potential in continuous immobilized fermentation. Overall, the biofilm engineering here represents an effective strategy to improve hEGF secretion and production, and can be adapted to produce more recombinant proteins in future.Article Title